THE INFLUENCE OF WORK DISCIPLINE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT THE SUB-DISTRICT OFFICE IN TANGERANG CITY - Abdul Azis; Dewi Sartika; Raden Yeti Sumiaty (Asosiasi Dosen Muda Indonesia, 2024)
The purpose of this research is to determine how job satisfaction and work discipline affect the performance of employees at the district office in Tangerang. This study uses a quantitative approach with a sample of 94 respondents, selected using the Slovin sampling method. Data collection was conducted through questionnaires. The results indicate that work discipline has a positive and significant impact on employee performance partially. From the first hypothesis test, the value of t-statistics exceeds the critical value, showing that the work discipline variable partially affects employee performance. In addition, the results of the simple regression test also support the conclusion that the significance value is less than the set threshold, leading to the rejection of the null hypothesis and the acceptance of the alternative hypothesis. Furthermore, the job satisfaction variable was also found to have a partial effect on employee performance, based on the second hypothesis test. The results of the simple regression test show a significant relationship, confirming that job satisfaction affects employee performance. Based on the joint hypothesis test, the value of F-statistics exceeds the critical value, indicating that both job satisfaction and work discipline variables simultaneously influence the performance of employees at the district office in Tangerang.